A superheater creep-fatigue interaction failure and its stress assessment. (January 2021) - Liu, William
Highlights: Creep-fatigue interaction failure in a superheater has been studied. Fractographic analysis identified the different creep fracture modes. The dynamic stress was calculated with the fracture orientation angle. In combination of the facture-mechanism map with the stress level and the fracture modes, fracture sequence was revealed. The two cracks initiated neither simultaneously nor at the same stress level. Abstract: Creep-fatigue interaction (CFI) is a common failure mode in turbine blades. However, this failure mode has rarely been reported in boiler superheaters. This article presents a failure analysis of CFI on a superheater in a black liquor-fired boiler. Two cracks in the HAZ of stitch weld were identified. The "beach marks" on fracture surfaces indicated the cyclic stress. Fractographic analysis distinguished the different fracture modes. Crack 1 initiated and propagated in the transgranular mode. Crack 2 initiated in intergranular mode and propagated in the mixture of intergranular and transgranular modes. On the base of the hoop stress and axial stress, the dynamic stress was the main root cause of CFI fracture. The dynamic stress can be calculated from the fracture orientation angle. The greater the fracture orientation angle, the higher the dynamic stress. The fracture-mechanism map was applied in this case study. In combination of fractographic analysis and stress calculation with the fracture-mechanism map, the crack fracture sequence was revealed. The two cracks did not initiate simultaneously, and their stress levels were significantly different. Through this case study the fracture-mechanism map was recommended as a guide to superheater fracture analysis.